Analysis of Immunotherapy in hepatocellular carcinoma - Burgos-Molina, Antonio Manuel; Alamilla Presuel, Juan Carlos; González Vidal, Alejandro; Ruiz-Gómez, Miguel José (Aseica, 2022)
One reason immunotherapy is important for Hepatocellular carcinoma, it’s because there are many immune cells in that organ. Because HCC is very aggressive, immunotherapy must be applied correctly. There are a lot of immunotherapies for all cancers, nevertheless, some has been tested for specific organs or tissues, and probably in the future, this organ-specific treatments can be applied in other tumor tissues.
Keywords: Inmunoterapia - Congresos; Cancer - Congresos; Immunotherapy; Hepatocellular cancer